Una especie nueva de Diplocentrus Peters, 1861 (Scorpiones: Diplocentridae) del estado de Sonora, México - Villa-Corella, Héctor Hugo; Silva-Kurumiya, Hugo; Barrales-Alcalá, Diego; Van Devender, Thomas R.; Francke, Oscar Federico (Instituto de Ecología, A.C., 2023)
A new species of scorpion, Diplocentrus leptomanus sp. nov., is described from northeastern Sonora, Mexico. This contribution increases the number of species in the genus Diplocentrus present in the state to five, two of which are endemic to the state. Morphological comparisons are provided with other species in the region, Diplocentrus williamsi Sissom & Wheeler, 1995, Diplocentrus peloncillensis Francke, 1975, and Diplocentrus spitzeri Stahnke, 1970.